Opportunities for the use of industrial ecology principles for environmental management in developing countries: A case study of Matsapha Industrial Estate in Swaziland - Dlamini, Mboni Zacharia (My University, 2006)
Human activity is characterised by the use of energy and materials to produce goods and services with wastes as by products. Population growth and development has increased the requirement of materials and energy which means more wastes. Industrial development has lead to a faster conversion of material and energy which means even more wastes. This has caused significant negative environmental impacts that are threatening natural resources and ecological balance from which the required materials are obtained. Developing countries are faced with the difficulty of balancing economic development and environmental protection. A development programme that is based on prioritising economic development at the expense of the environment is not sustainable. The main objective of this research is to investigate the potential of using industrial ecology principles to address the environmental problems of developing countries. This is done by using a case study of Matsapha Industrial Estate in Swaziland. The term industrial ecology is derived from an analogy to biological ecosystems, in which waste from one organism is food to another making the system sustainable because of the closed waste loop. Braden Allenby (1992) defines industrial ecology as: “Industrial Ecology may be defines as the means by which a state of sustainable development is approached and maintained. It consists of a systems view of human economic activity and its interrelationship with fundamental biological, chemical and physical systems with the goal of establishing and maintaining the human species at levels that can be sustained indefinitely, given continued economic, cultural and technological evolution”. Using a cross sectional data set, appropriate environmental performance indicators of the case study area were determined. Three broad categories of environmental performance indicators are used. These are: - Resource Use - Emissions - Management of Community Interactions The investigation of the opportunities of using industrial ecology principles in the case study area is done by setting up scenarios where the principles are applied. The results are then compared with established environmental performance indicators. The industrial ecology principles considered are: - Systems Approach - Industrial Symbiosis - Industrial metabolism - Integrated Approach - Diversity or Flexibility - Shared resources Of the six, five were applied. Industrial metabolism was not applied because of the scope of the research. The research indicates that the use industrial ecology principles do improve the environmental performance of the case study with some economic benefits. The research also revealed that industrial ecology improves the interaction between the three components of industrial ecosystems i.e. the industrial activity, the social and the ecological or environmental component thus establishing the foundation for sustainable development. It is also revealed that industrial ecology provides the means of moving towards closing the waste loop in a way that recognises the importance of balancing the economic objectives of industrial activities and the environmental objectives of the public sector as well as the social responsibility of both the industrial and public sector. The research recommends that industrial ecology principles be used to address the environmental problems of the case study area because of the many benefits that would be realised particularly the achievement of both economic and environmental objectives. The main recommendations of the research for the case study area are: - Identification of the Industrial Estate Manager. The recommended industrial estate manager in the case study area is the existing Matsapha Town Board. It is therefore not an individual but an institution. This institution would be the organising force that will facilitate and coordinate the interaction between the three components of the eco-industrial system. - Resource Recovery in the form of recycling be the eco-industrial theme because of the absence of an anchor industry. - Further research focused on industrial metabolism and use of various wastes as inputs for other industries
Student Number : 0313728F - MSc research report - School of Civil and Environmental Engineering - Faculty of Engineering and the Built Environment
Keywords: industrial ecology; environmental management